Some Rural Attractions which Attract Tourists - Chi, Shu-Yi; Huang, Biing-Wen; Luo, Han Xing (Asian Journal of Agriculture and Rural Development, 2019)
Developing rural tourism is a comprehensive strategy for improving the rural economy. The Structure Equation Model (SEM) approach was applied to test how attraction and experiential values of a rural region affect the tourists’ satisfaction and their decision to revisit. After interviewing 353 tourists during their trip to Hakka County, Miaoli, Taiwan, the new finding of this study is that rural life and culture are more attractive than rural scenery to tourists. This implies a strong preference for tourists to experience agricultural knowledge and engage with rural life and farming work. Furthermore, the experiential response generated from the indirect mediation effect of satisfaction had a significant effect, supporting the concept that satisfaction brings additional experiential values to the intentions of tourists to revisit and thus creates more revisit opportunities to those tour sites.